2012
DOI: 10.1371/journal.pone.0051988
|View full text |Cite
|
Sign up to set email alerts
|

Different Transcriptional Profiles of RAW264.7 Infected with Mycobacterium tuberculosis H37Rv and BCG Identified via Deep Sequencing

Abstract: BackgroundThe Mycobacterium tuberculosis H37Rv and BCG effects on the host cell transcriptional profile consider a main research point. In the present study the transcriptome profiling analysis of RAW264.7 either infected with Mycobacterium tuberculosis H37Rv or BCG have been reported using Solexa/Illumina digital gene expression (DGE).ResultsThe DGE analysis showed 1,917 different expressed genes between the BCG and H37Rv group. In addition, approximately 5% of the transcripts appeared to be predicted genes t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
6
0

Year Published

2013
2013
2022
2022

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 10 publications
(9 citation statements)
references
References 49 publications
(54 reference statements)
3
6
0
Order By: Relevance
“…Only one gene (Pbr000187.1) did not show consistent expression between accurate quantification of expression and digital transcript abundance measurements (Additional file 5). Pearson’s correlation coefficient (r) showed that both the digital transcript abundance measurements and qRT-PCR data were highly correlated, with the r-value ranging from 0.656 (Pbr036692.1) to 0.934 (Pbr001279.1), which was in agreement with previous report [52]. The qRT-PCR further demonstrated that genes related to photosystem reaction (Pbr041327.1), hormone-related transcripts (Pbr036692.1), carbohydrate metabolism (Pbr021608.1, Pbr008092.1, and Pbr001279.1) and other differentially regulated genes (Pbr027181.1) showed significant difference between treatments and participated in the process of calyx abscission or persistent processes.…”
Section: Resultssupporting
confidence: 91%
“…Only one gene (Pbr000187.1) did not show consistent expression between accurate quantification of expression and digital transcript abundance measurements (Additional file 5). Pearson’s correlation coefficient (r) showed that both the digital transcript abundance measurements and qRT-PCR data were highly correlated, with the r-value ranging from 0.656 (Pbr036692.1) to 0.934 (Pbr001279.1), which was in agreement with previous report [52]. The qRT-PCR further demonstrated that genes related to photosystem reaction (Pbr041327.1), hormone-related transcripts (Pbr036692.1), carbohydrate metabolism (Pbr021608.1, Pbr008092.1, and Pbr001279.1) and other differentially regulated genes (Pbr027181.1) showed significant difference between treatments and participated in the process of calyx abscission or persistent processes.…”
Section: Resultssupporting
confidence: 91%
“…The results showed that although the exact fold changes for the selected genes at three stages varied between digital gene expression and qRT-PCR analysis, the trend of gene expression changes detected by the two different approaches were largely consistent (Figure 5 ). Pearson's correlation coefficients showed that the digital transcript abundance measurements and qRT-PCR data were highly correlated (Table 7 ), with R 2 -values ranging from 0.639 ( Pbr027485.1 ) to 0.998 ( Pbr004885.1 ), which was in agreement with previous reports (Pan et al, 2012 ).…”
Section: Resultssupporting
confidence: 91%
“…To date, however, the molecular mechanism of Sp110-mediated macrophage resistance to Mtb remains unknown, and the downstream genes involved in Sp110-mediated pathways are unexplored. Most recently, high-throughput sequencing and microarray technologies have been introduced to analyse the mammalian host response to mycobacterial pathogens, the results of which have greatly enhanced scientific understanding of the interactions occurring between host species and pathogens 2 28 29 30 31 32 . Because macrophages are the main host cells for Mtb , efficient genetic manipulation of them is required to investigate innate immunity to this pathogen, but achieving this is especially difficult in primary macrophages.…”
Section: Discussionmentioning
confidence: 99%